FAKTOR PENGHAMBAT PENGOBATAN PASIEN TUBERKULOSIS PARU DI PUSKESMAS KECAMATAN TAPA KABUPATEN BONE BOLANGO: Tuberkulosis merupakan penyakit menular yang disebabkan oleh infeksi bakteri Mycobacterium tuberculos. kelompok Mycobacterium yaitu Mycobacterium tuberculosis. Terdapat beberapa spesies Mycobacterium, antara lain: M. tuberculosis, M. africanum, M. bovis, M. leprae. Tujuan penelitian ini untuk mengetahui apa saja factor yang menjadi Penghambat Pengobatan pasien Tuberkulosis Paru di Puskesmas - Rasdianah, Nur; Taupik, Muhammad; Djuarno, Endah Nurrohwintah; Hutuba, Ariani; Manno, Mohamad Reski; molote, kasibee molote (Jurnal Literasi Mandiri, 2025)
Tuberculosis is an infectious disease caused by infection with the bacteria Mycobacterium tuberculos. The Mycobacterium group is Mycobacterium tuberculosis. There are several species of Mycobacterium, including: M. tuberculosis, M. africanum, M. bovis, M. leprae. The purpose of this study was to determine what factors inhibit the treatment of pulmonary tuberculosis patients at the Tapa District Health Center, Bone Bolango Regency. This research method is qualitative descriptive with Purposive Sampling sampling with inclusion criteria. Data analysis uses data reduction, data presentation, drawing conclusions/verification. The results of the study based on the experience of consuming medication, patients have several symptoms that can be inhibiting factors for treatment, namely two patients with itching, five patients with nausea, two patients with body aches and two patients with poor appetite. As for the obstacles and barriers when consuming medication, there are five patients out of 15 patients who have obstacles, namely P1 feels hot, P2 feels pain when coughing, P3 feels vomiting, P4 feels chest pain, red urine and often thirsty, and P5 feels no appetite. And the drugs prescribed for all respondents are in accordance with the health services at the Tapa Community Health Center, which are very good.